Analisis Kualitas Video Pembelajaran Berdasarkan Teori Multimedia Mayer - Atya Anindita Lukman Putri; Agus Lestari (PT. AHLAL PUBLISHER NUSANTARA, 2025)
The development of digital technology has encouraged the use of multimedia as an effective learning strategy. However, the effectiveness of multimedia is greatly influenced by its suitability to the cognitive principles described in Mayer's Cognitive Theory of Multimedia Learning (CTML). This study aims to analyze how Mayer's multimedia principles are applied in an educational video titled